2017
DOI: 10.1093/molbev/msx258
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing of African Dogs Provides Insights into Adaptations against Tropical Parasites

Abstract: Natural selection in domestic dogs is of great interest in evolutionary biology since dogs have migrated to every inhabited continent of the world alongside humans, and adapted to diverse environments. Here, we explored their demographic history and genetic basis of adaptation to the tropical African environment using whole genome analyses of 19 African indigenous dogs from Nigeria. Demographic analysis suggests that the ancestors of these dogs migrated into Africa from Eurasia 14,000 years ago and underwent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 90 publications
5
41
0
Order By: Relevance
“…A mutation rate of 2.2 × 10 −9 per site per year with a generation time of 3 years was assumed. Since our demographic analysis did not include wolves and European breeds, the effective population sizes and split time for wolves and European breeds were taken from Wang et al 3 and Liu et al 83 .…”
Section: Methodsmentioning
confidence: 99%
“…A mutation rate of 2.2 × 10 −9 per site per year with a generation time of 3 years was assumed. Since our demographic analysis did not include wolves and European breeds, the effective population sizes and split time for wolves and European breeds were taken from Wang et al 3 and Liu et al 83 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, outside of ESS, there have been no breed-specific analyses. Considering that different WGS efforts in dogs have recently proven to be advantageous in elucidating genetic susceptibility to disease [22][23][24][25][26][27], differences in body types [28], as well as adaptions against parasites [29], we have compiled and processed WGS data to begin the exploration of breed-specific CMT-risk alleles and, in this initial report, to specifically reveal the coding variants detected in orthologs of the high-risk human breast cancer susceptibility genes.…”
Section: Introductionmentioning
confidence: 99%
“…Little is still known about basic biological and ecological aspects of the African wolf because of its previous misidentification as a golden jackal (Canis aureus). Recent phylogenetic studies conducted on the species identified two main populations in Northwestern and in Eastern Africa [12][13][14][15]21,22]. The demographic history of the species, however, remains unknown to date.…”
Section: Introductionmentioning
confidence: 99%